Revitalising English Teacher Education through Blended Learning: A Boon or Bane? - Islam Ahmad Sukri, Saiful; Md. Yunus, Melor (International Journal of Engineering and Technology, 2018)
Presently, there are a growing trend and accrued interest to optimize education through technology. More specifically, there is a paradigm shift to integrate online learning with classroom training, resulting in the conception of blended learning. Nevertheless, the Government’s multi-million investments to increase the use of ICT and teachers’ ICT literacy skills has incessantly been of little fruition and this has raised an unabated concern for the utilization of online learning in an in-service training programme for English teachers or more popularly known as Pro-ELT ((Professional Up-skilling of English Language Teachers). Thereby, this paper intends to survey the English teachers’ perceptions of the use of online learning in the Pro-ELT Programme. The findings indicated that the majority of respondents reacted positively to the incorporation of online learning in the aforesaid programme. However, there is a vocal chorus of concern about, inter alia, the Internet accessibility, the ease of online learning platform and its friendliness. The paper culminates with implications of the study and suggestions for future research.